The contribution of ICT in teaching and learning Tone of Tanzanian Bantu languages - Ismail, Joseph Hokororo (Machakos University, 2019)
This paper was intended to discuss the contribution of Information Communication Technology (ICT) in teaching and learning tone of a given language. The paper urges that apart from depending only traditional education technology and methodology in learning and teaching, ICT can contribute successfully in teaching and learning tone. In traditional perspectives, it is believed that teaching and learning of subject matters is very much related and necessitated by offering training on formal settings which involve classroom interaction an organized classroom with hardcopy books and other related matters. With the development of ICT, and the rise of network, the correspondence and interaction through networking has expanded globally. One of the tools used in teaching and learning of Tone is ICT, specifically Computer. The theoretical framework adopted in this paper are Classic learning theories which include behaviorism (Skinner, 1953), Cognitivism (Gagne, 1984) (Akinsanmi, 2008). Qualitative approach was employed to involve the researcher’s interpretation of linguistic narrative data which were obtained from the documentary reviews and focus group discussions done by respondents both students and instructors on tone class by giving them freedom of expression on how ICT was facilitated them tone learning. The study was carried out in two programes in MA. Linguistics class, in one university. This study used three methods such as focus group discussion, interview and documentary review.The findings of the study were: (i) that ICT facilitates teaching of tone through application of symbols and equations that couldn’t be possible or difficult in using free hand drawings, (ii) easy manipulation of sounds and tone marking strategies of which the mechanical listening of sounds through ear that may miss- lead tone interpretation has facilitated the accuracy tone analysis. The conclusions drawn from this study were that the Institutions which are involved in teaching tonology can get use of ICT technology in a very formal way thus contributing to high level of mastering the of subject matter with a minimum time waste. The paper recommends that both learners and instructors should be ICT illiterate and get use of it as through establishing computer laboratory to enable students to have an access to computer facilities, thus contributing to sustainable development in terms of human resource utilization and innovation.
Keywords: ICT; Network; Social media; Language; Teaching; Tonology; Bantu